2011
DOI: 10.1371/annotation/3ac615cc-2ecf-4d3e-9281-3b9b9b04cf08
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Does Environmental Enrichment Reduce Stress? An Integrated Measure of Corticosterone from Feathers Provides a Novel Perspective

Abstract: Enrichment is widely used as tool for managing fearfulness, undesirable behaviors, and stress in captive animals, and for studying exploration and personality. Inconsistencies in previous studies of physiological and behavioral responses to enrichment led us to hypothesize that enrichment and its removal are stressful environmental changes to which the hormone corticosterone and fearfulness, activity, and exploration behaviors ought to be sensitive. We conducted two experiments with a captive population of wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 71 publications
3
12
0
Order By: Relevance
“…As predicted, in the two zoos in which cranes were observed to intentionally attack the flamingos (i.e., zoos K and L) the highest CORTf values were measured. This supports the hypothesis that repetitive and/or severe stressful events can have a measurable influence on CORTf [32,33].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As predicted, in the two zoos in which cranes were observed to intentionally attack the flamingos (i.e., zoos K and L) the highest CORTf values were measured. This supports the hypothesis that repetitive and/or severe stressful events can have a measurable influence on CORTf [32,33].…”
Section: Discussionsupporting
confidence: 86%
“…However, results have consistently led to the conclusion that CORTf is a useful measure to show HPA-axis reactions to stimuli in order to predict an alteration in allostatic load. Fairhurst et al [33] were able to show a short-term increase of CORTf followed by a long-term decrease in Clark's Nutcrackers (Nucifraga columbiana) in response to enrichment. Will et al [46] measured elevated CORTf levels in food-deprived Rhinoceros Auklet (Cerorhinca moncerata) chicks.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As described in a study by Bortolotti et al and then confirmed in other studies, increased plasma CORT levels during feather growth result in elevated CORTf levels [11][12][13][14]. To determine CORTf, the feathers are sampled by plucking them from live or dead birds or even by collecting the ones dropped by molting birds [10,11,13,15]. Depending on the scientific context, the aspect of a long-term and retrospective view on the activity of the HPA axis could be a clear benefit compared to other corticosterone measurement methods.…”
Section: Introductionmentioning
confidence: 93%
“…A year after Burden et al’s paper [ 172 ], Zemanova [ 176 ] published a paper bringing together copious examples of available and innovative alternative methods, i.e., showing the principle of the three Rs at work, be this in genetic or behavioral studies. Zemanova demonstrated convincingly that methods are already available that are non-invasive and superior in producing reliable data [ 176 ]: For example, instead of capturing birds and taking blood samples (both highly invasive and stressful strategies for mammals and birds alike [ 177 ]), various studies have found that excrements [ 178 , 179 ] and feathers [ 180 , 181 ] can produce reliable results without subjecting the bird to invasive procedures [ 182 ]. In foxes it was demonstrated that DNA could be extracted from their footprints in the snow and, thus, did not require trapping and handling them [ 183 , 184 ].…”
Section: In Situ and Ex Situ Conservationmentioning
confidence: 99%